Comparison of Static and Dynamic Stability in Undergraduate Physiotherapy Student of Hyderabad And Jamshoro Sindh - Bakhtawar Samejo; Fahad Farooq Lasi; Muhammad Hassan Waseem (Journal Riphah College of Rehabilitation Sciences, 2019)
Background: Basic daily activities include balance and coordination. Lack of balance can be a major risk factor of injuries related to daily activities. The classification of balance is static balance and dynamic balance.